2007
DOI: 10.1083/jcb.200608077
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of DNA-PKCS regulates its dynamics at DNA double-strand breaks

Abstract: The DNA-dependent protein kinase catalytic subunit (DNA-PKCS) plays an important role during the repair of DNA double-strand breaks (DSBs). It is recruited to DNA ends in the early stages of the nonhomologous end-joining (NHEJ) process, which mediates DSB repair. To study DNA-PKCS recruitment in vivo, we used a laser system to introduce DSBs in a specified region of the cell nucleus. We show that DNA-PKCS accumulates at DSB sites in a Ku80-dependent manner, and that neither the kinase activity nor the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
422
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(449 citation statements)
references
References 36 publications
(86 reference statements)
23
422
1
3
Order By: Relevance
“…2B). Likewise, DNA-PKcs autophosphorylation at Ser 2056 (27) increased when PEO1 cells were treated with ABT-888 (Fig S2A), and this phosphorylation was reversed by DNA-PK inhibition ( Fig. S2 B and C).…”
Section: Parp Inhibitor Synthetic Lethality Is Independent Of Xrcc1 Amentioning
confidence: 92%
“…2B). Likewise, DNA-PKcs autophosphorylation at Ser 2056 (27) increased when PEO1 cells were treated with ABT-888 (Fig S2A), and this phosphorylation was reversed by DNA-PK inhibition ( Fig. S2 B and C).…”
Section: Parp Inhibitor Synthetic Lethality Is Independent Of Xrcc1 Amentioning
confidence: 92%
“…Laser microirradiation was carried out with a pulsed nitrogen laser (Micropoint Ablation laser system; Photonic Instruments Inc.) coupled to a Zeiss Axiovert200M microscope and focused through a PlanApochromat 63ϫ/NA 1.40 oil immersion objective (44). The output laser power was set at 75% of maximum, which creates double-stranded breaks (DSBs) (as confirmed by ␥H2AX staining) and induces accumulation of EGFP-tagged RFWD3 in living cells.…”
Section: Methodsmentioning
confidence: 99%
“…Live cell imaging of DNA repair proteins induced with a micro-laser is now widely used to study the kinetics of DNA damage responses [38][39][40] . Live cell imaging with heavy ions has shown that DNA repair proteins are recruited at sites of heavy ion hits in cell nuclei of fibroblast cells within seconds, and no large scale chromatin movements are associated to the repair activity 41 , yet some movement is observed in the repair protein foci.…”
Section: Dna Damagementioning
confidence: 99%